2014
DOI: 10.3389/fnmol.2014.00066
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine-induced tyrosine phosphorylation of NR2B (Tyr1472) is essential for ERK1/2 activation and processing of novel taste information

Abstract: Understanding the heterosynaptic interaction between glutamatergic and neuromodulatory synapses is highly important for revealing brain function in health and disease. For instance, the interaction between dopamine and glutamate neurotransmission is vital for memory and synaptic plasticity consolidation, and it is known to converge on extracellular signal-regulated kinase (ERK)-MAPK signaling in neurons. Previous studies suggest that dopamine induces N-methyl-D-aspartate (NMDA) receptor phosphorylation at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 73 publications
13
31
0
Order By: Relevance
“…Dopamine-induced cAMP/PKA pathway enhances the electrophysiological effects of ongoing glutamatergic input onto MSN dendritic spines by modulating ion channels within synapses (Surmeier et al, 2007) that increases calcium-dependent ERK activation leading to c-fos promoter activation. One biochemical mechanism involves D1/cAMP/PKA phosphorylation of NMDA receptors in the synapse to enhance activation of the NMDA/calcium/ERK pathway (David et al, 2014; Ron, 2004). Another biochemical mechanism proposes that D1/cAMP/PKA activates a DARPP32-mediated mechanism that indirectly enhances NMDA/calcium activation of the ERK pathway (Valjent et al, 2005).…”
Section: Molecular and Cellular Mechanisms Of Drug-induced C-fos Pmentioning
confidence: 99%
“…Dopamine-induced cAMP/PKA pathway enhances the electrophysiological effects of ongoing glutamatergic input onto MSN dendritic spines by modulating ion channels within synapses (Surmeier et al, 2007) that increases calcium-dependent ERK activation leading to c-fos promoter activation. One biochemical mechanism involves D1/cAMP/PKA phosphorylation of NMDA receptors in the synapse to enhance activation of the NMDA/calcium/ERK pathway (David et al, 2014; Ron, 2004). Another biochemical mechanism proposes that D1/cAMP/PKA activates a DARPP32-mediated mechanism that indirectly enhances NMDA/calcium activation of the ERK pathway (Valjent et al, 2005).…”
Section: Molecular and Cellular Mechanisms Of Drug-induced C-fos Pmentioning
confidence: 99%
“…Recent results by David et al . () suggest that the dopamine D1 receptor‐evoked NR2B phosphorylation at Tyr1472 not only correlates well with the D1R‐evoked ERK1/2 activation, but it is also necessary for it.…”
Section: Resultsmentioning
confidence: 90%
“…Our results further demonstrated that stimulation of dopamine D1 receptors in hippocampal slices also induces a significant increase in both ERK1/2 activation and NR2B(Tyr1472) phosphorylation, confirming the data of David et al . (). Moreover we have shown for the first time that the D1R‐mediated ERK1/2 activation and NR2B(Tyr1472) phosphorylation occur under the permissive control of A 2A receptors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations